A Proposal for the Pollution Management Reform in Lithuania: “Pollution Currency” Approach (part 2) - Čekanavičius, Linas (Ekonomika, 1998)
The previously introduced idea of a universal “pollution currency” that should be used for “payments” for the right to emit specified types of pollutants into air or water (see previous volume of “Ekonomika”) is developed here. It is demonstrated that the universal and transferable emission coupons (UTEC) concept actually integrates the main advantages of emission taxes and marketable pollution permits systems, while avoiding some of their less desired qualities.